When green and red mycology meet: Impressions from an interdisciplinary forum on virulence mechanisms of phyto- and human-pathogenic fungi - Yu, Yidong; Hube, Bernhard; Kämper, Jörg; Meyer, Vera; Krappmann, Sven (Virulence, 2017)
Fungal infections pose a constant threat to plants and humans, but detailed knowledge about pathogenesis, immunity, or virulence is rather scarce. Due to the fact that a certain overlap in the armoury of infection exists between plant- and human-pathogenic fungi, an interdisciplinary forum was held in October 2016 at the Institute for Clinical Microbiology, Immunology and Hygiene in Erlangen under the organisational umbrella from two special interest groups of German microbial societies. Scientific exchange and intense discussion of this timely topic was fostered by bringing together renowned experts in their respective fields to present their thoughts and recent findings in the course of a plenary lecture and six themed sessions, accompanied by oral and poster contributions of young researchers. By targeting the topic of fungal virulence mechanisms from various angles and in the context of plant and human hosts, some common grounds and exciting perspectives could be deduced during this vibrant scientific event.
EVALuna2:7738